The Europeanisation of reference groups: A reconsideration using EU-SILC - Christopher T. Whelan; Bertrand Maître (The Economic and Social Research Institute (ESRI), 2007)
In this paper we address the question of the relative importance of within and between country differences in income and material deprivation in the European Union in the context of recent suggestions that insufficient attention has been paid to cross-national differences. In particular, we respond to the argument that the 'state bounded' relative income approach obscures the significance of EU-wide reference groups. Making use of EU-SILC 2004, we have sought to quantify the magnitude of relevant within and between country differences and their relative impact. Overall, our analysis supports the view that the predominant frame of reference is a national one. The limited impact of European reference groups observed in our analysis does not require explanation in terms of the emergence of a European social stratification system. Furthermore, the significance of such comparisons depends not only on the expectations of those affected by European inequalities but on the degree of legitimacy afforded to ensuing demands. While an EU-wide income-threshold can provide information regarding progress of the Union towards greater social cohesion, its usage for this purpose does not require a strong sense of European identity. Given, the current status of the European Social Model it would seem unwise to attribute an undue degree of policy relevance to the relatively modest evidence relating to the impact of EU-wide reference groups revealed in our analysis.
Keywords: 330; reference groups; income poverty; economic strain; economic stress; Einkommensverteilung; Privater Haushalt; Messung; Vergleich; EU-Staaten